2013
DOI: 10.1182/blood-2012-05-432989
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Jak2V617F myeloproliferative neoplasm-propagating stem cells by interferon-α in a murine model of polycythemia vera

Abstract: Key Points• IFNa targets Jak2V617F MPN stem cells.Interferon-a (IFNa) is an effective treatment of patients with myeloproliferative neoplasms (MPNs). In addition to inducing hematological responses in most MPN patients, IFNa reduces the JAK2V617F allelic burden and can render the JAK2V617F mutant clone undetectable in some patients. The precise mechanism underlying these responses is incompletely understood and whether the molecular responses that are seen occur due to the effects of IFNa on JAK2V617F mutant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
118
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(133 citation statements)
references
References 55 publications
(82 reference statements)
12
118
0
1
Order By: Relevance
“…The Li 2010 model presented with fewer phenotypic HSCs that were compromised in their reconstitution ability and self-renewal and had accumulated DNA damage, 20,34 whereas the Mullaly 2010 model observed no impact on HSC competitiveness despite an altered cycling status. 36,37 In the Marty 2010 model, an increase in HSC competitiveness was reported, 33 whereas the Tiedt 2008 model showed a complex HSC phenotype with an increase of phenotypic long-term HSCs that were less competitive, expressed a short-term HSC gene signature, and presented with an increase in DNA damage. 35 Using the Li et al and Kent et al models, 20,21,34 in which a HSC defect had been observed, it was striking to see that nascent HSCs are completely unaffected by the JAK2V617F mutation, even when present in 2 copies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Li 2010 model presented with fewer phenotypic HSCs that were compromised in their reconstitution ability and self-renewal and had accumulated DNA damage, 20,34 whereas the Mullaly 2010 model observed no impact on HSC competitiveness despite an altered cycling status. 36,37 In the Marty 2010 model, an increase in HSC competitiveness was reported, 33 whereas the Tiedt 2008 model showed a complex HSC phenotype with an increase of phenotypic long-term HSCs that were less competitive, expressed a short-term HSC gene signature, and presented with an increase in DNA damage. 35 Using the Li et al and Kent et al models, 20,21,34 in which a HSC defect had been observed, it was striking to see that nascent HSCs are completely unaffected by the JAK2V617F mutation, even when present in 2 copies.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the JAK2V617F mutation on HSCs has been studied 20,21,[33][34][35][36][37] and was shown to compromise HSC function in one model, 20,34 a defect that is even more severe when homozygous. 21 Using the model, in which JAK2V617F is expressed from the mouse endogenous Jak2 locus following recombination with Stella-Cre, 21 we set out to determine how constitutively active JAK2 would affect embryonic HSPCs.…”
Section: Agm Hscs Are Resistant To the Effects Of The Jak2v617f Mutationmentioning
confidence: 99%
“…29 Flow cytometry and gene expression data demonstrate that this effect is mediated by the forced differentiation of neoplastic stem cells. The consequent exhaustion of the stem cell pool leads to a decrease of extra-medullary hematopoiesis, with a significant improvement of spleen size.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in myeloproliferative neoplasms, the therapeutic activity of recombinant interferon-α seems to be mediated more by the direct suppressive effects on neoplastic stem cells than by anti-inflammatory and/or immunoregulatory mechanisms. [29][30][31] The latter may, however, contribute to the clinical and histological response to recombinant interferon-α therapy, considering that increased levels of pro-inflammatory cytokines have an important role in the pathobiology of myeloproliferative neoplasms. 32 The interferon-mediated decrease of serum cytokines may thus resemble the anti-inflammatory effects of ruxolitinib, which are thought to be responsible for the improvement of spleen size after ruxolitinib administration.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical data in mice model support that IFN preferentially depletes Jak2V617F MPN-propagating stem cells by activating cell cycle and promoting a predetermined erythroid-lineage differentiation program [6]. This was later shown to occur in humans by Prchal [7].…”
mentioning
confidence: 90%